Feminism and Bourdieusian Social Theory in a Sexual Health Empowerment Project with Incarcerated and Recently Released Women - Emerson, Amanda M. (Soc Theory Health, 2018)
Theory is often downplayed or omitted in the research and scholarly literature around public health interventions in carceral settings. Our Sexual Health Empowerment (SHE) project was an education intervention and ethnographic study that aimed to reduce cervical cancer risk among women with histories of incarceration. In this article, we describe our application of concepts from feminist theory and bourdieusian social theory to the design, planning, and delivery of SHE. We outline how theory-driven practice both underscored and helped us meet challenges in implementation in three urban jails over a two-year period, 2014–2016. Our approach provides a model for others who wish to bring critical theory and research practice together in health interventions with populations that are marginalized in multiple ways.